Information Provision and Support for Inheritance Taxation: Evidence from a Representative Survey Experiment in Germany - Luna Bellani; Kattalina Berriochoa; Mark Kapteina; Guido Schwerdt (Institute of Labor Economics (IZA), 2024)
We study the effects of information on attitudes towards inheritance taxation using survey experiments fielded in Germany. We show that information about tax allowances increases demand for higher taxes and shifts public opinion from favoring abolition to supporting the tax. Effects are primarily due to a prevalent underestimation of tax allowances and the alteration of people's expectations of being affected by such taxes. In contrast, information highlighting the increasing proportion of inherited wealth only negligibly affects policy demand. Our results suggest that pocketbook motives and misinformation may contribute to explaining the paradox of limited demand for inheritance taxation despite growing inequality concerns.
Keywords: H20; D72; D83; 330; capital taxation; equality of opportunity; inheritance tax; information; randomized experiment